Are Women Doing It for Themselves? Female Managers and the Gender Wage Gap. (8th June 2022) - Theodoropoulos, Nikolaos; Forth, John; Bryson, Alex
ABSTRACT: Using linked employer‐employee data for Britain, we find a robust association between the share of female managers in the workplace and the size of the gender wage gap. In workplace fixed‐effects estimates, the gap is eradicated when more than 60% of workplace managers are women, a scenario that obtains in around one fifth of all workplaces. The association between the share of female managers and the gender wage gap is more pronounced when workplace managers set pay at the workplace, and where employees are paid for performance. These findings are consistent with the proposition that women are more likely to be paid equitably when managers have discretion in the way they set pay or reward performance and those managers are women. They suggest that a stronger presence of women in managerial positions can help tackle the gender wage gap.